Experimental investigation of solar-driven double ejector refrigeration system - Visedmanee, Jedsada; Pongtornkulpanich, Anan; Somkun, Sakda; U-kaew, Ananchai (Journal of Renewable Energy and Smart Grid Technology, 2015)
Basic single-stage ejector refrigeration system has been one of the attractive thermal refrigeration systems, because it works with solar assistance, resembles with a vapor compression refrigeration system, uses single pure refrigerant and easy to construct. However, the system performance, which is defined as coefficient of performance, COP, has been traditionally low. In order to promote this type of thermal refrigeration system as another choice in cooling market, the solar-driven double ejectors refrigeration system, in this research, has been developed from basic unit and fabricated to be experimentally tested. The computer simulation program of double ejectors refrigeration system has been developed to simulate various parameters such as optimum mass flow rate of entrained fluid, load at condenser, boiler, evaporator, ejector performance, COP and dimensions of ejector to be used for system design. Double ejector system, which differs from one ejector for single stage, uses two identical ejectors placed parallel in the system. Saturated boiling steam at 110oC is used to primary vapor to drive ejectors and evaporator condition uses at temperature of 10oC.From the comparison of experimental results between single and double ejector system, it was found that COP of double ejector system was 15% higher than single system.